P767 Sex, drugs and the internet – the perfect storm for syphilis transmission among black gay and bisexual men (BMSM). (14th July 2019) - Jennings, Jacky; Tilchin, Carla; Schumacher, Christina; Hamill, Matthew; Latkin, Carl; Rompalo, Anne; Ruhs, Sebastian; Rives, Sarah; Fields, Errol; Greenbaum, Adena; Ghanem, Khalil
Abstract : Background: Use of the internet to meet sex partners has increased over time among MSM, and an outbreak of syphilis has been linked to seeking sex partners through an online chatroom. Other studies have shown associations between methamphetamine use(MU), sexual risk behaviors and STIs including syphilis. The objective was to determine the association between syphilis positivity, MU, sexual risk behaviors and sex partner meeting spaces and separately, MU, sexual risk behaviors and sex partner meeting spaces among Black MSM(BMSM) in one mid-Atlantic U.S. city without a known history of these associations. Methods: Data came from an ongoing longitudinal cohort study, the Understanding Sexual Health in Networks Study (USHINE) including MSM 18–45 years of age in Baltimore City. Information on MU and sex partners and meeting spaces in the past 3 months was obtained via an egocentric sexual network survey. Summary statistics, chi-squared tests and t-tests were used for hypothesis testing. Results: 147 MSM were enrolled and 75.5% (111) were BMSM. The mean age of participants was 29.7 years (SD 5.60); 33.3%(34) were syphilis positive. Syphilis positivity was associated with MU (57.1% vs 29.6%, p-value=0.042) and meeting sex partners on Jack'd (42.3% vs 23.4%, p-value=0.046) and Facebook (52% vs 27%, p-value=0.022). MU (vs no use) was associated with anonymous sex (69.2% vs 19.3%, p-value <0.000), higher numbers of sex partners (≥3 in past 3 months 76.9% vs 25.7%, p-value <0.001), and meeting sex partners on Jack'd (84.6% vs 47.7%, p-value=0.012), Grindr (69.2% vs 25.7%, p-value <0.001), and Adam4Adam (53.9% vs 15.6%, p-value <0.001). Conclusion: Among BMSM, syphilis infection was associated with MU and specific sex partner meeting spaces, and MU was associated with sexual risk behaviors and specific sex partner meeting spaces. The relationships have not been identified before in this setting and suggest specific meeting spaces may be important access points for syphilis and drug use prevention. Disclosure: No significant relationships.